2012
DOI: 10.1111/j.1582-4934.2011.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of COX‐2/PGE2 signalling in hypoxia‐induced angiogenic response in endothelial cells

Abstract: To evaluate the impact of hypoxia on the angiogenic capability of endothelial cells (ECs), and further investigate whether the cyclooxygenase-2 (COX-2)/prostaglandin E2 (PGE2) signalling is involved in the angiogenic response of ECs to hypoxia. We explored the impact of various periods (1, 3, 6, 12, 24 hrs) of hypoxia (2% O2) on human umbilical vein endothelial cells (HUVECs) in vitro. We observed cell viability, migration, tube formation, analysed COX-2, vascular endothelial growth factor (VEGF), AQP1 mRNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 70 publications
3
55
0
Order By: Relevance
“…The COX-2/PGE2 axis is a potential driver of HIF-2α expression and activity in HCC cells and HCC tissues under hypoxic conditions COX-2 is also upregulated in hypoxic HCC tissues and is associated with a poor prognosis in HCC patients; this relationship with HCC is similar to that of HIF-2α (10,11,16,18). COX-2 elicits its effects mainly through producing prostaglandins, especially PGE2 (20,21).…”
Section: Downregulation Of Hif-2α Inhibits the Tumour Development Andmentioning
confidence: 71%
See 1 more Smart Citation
“…The COX-2/PGE2 axis is a potential driver of HIF-2α expression and activity in HCC cells and HCC tissues under hypoxic conditions COX-2 is also upregulated in hypoxic HCC tissues and is associated with a poor prognosis in HCC patients; this relationship with HCC is similar to that of HIF-2α (10,11,16,18). COX-2 elicits its effects mainly through producing prostaglandins, especially PGE2 (20,21).…”
Section: Downregulation Of Hif-2α Inhibits the Tumour Development Andmentioning
confidence: 71%
“…Previous studies have also revealed that COX-2 can be induced by various stimuli, including hypoxia (15,16). In the context of HCC, COX-2 expression in tumour tissues is closely associated with the spontaneous initiation, development and treatment effects of HCC (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Another candidate is COX2 (cyclooxygenase 2), a target gene of NF-B (40). Prostaglandin E2, a product of COX2, increases microvascular permeability (41), and activation of the COX2/PGE2 pathway increases AQP1 mRNA expression in human umbilical vein endothelial cells (42).…”
Section: Discussionmentioning
confidence: 99%
“…Most solid tumors exhibit inflammatory properties characterized by increased levels of prostaglandins (Stasinopoulos et al 2013). Cyclooxygenase-2 (COX-2) is induced by the hypoxic microenvironment (Fredenburgh et al 2009;Kaidi et al 2006;Lee et al 2010;Zhao et al 2012). COX-2 increases metastatic potential in cancer cells and silencing of COX-2 inhibits metastasis and delays tumor onset of poorly differentiated metastatic cancer cells (Stasinopoulos et al 2013;Tsujii et al 1997).…”
Section: Introductionmentioning
confidence: 99%